"The Pearl Harbor of the Twenty-first Century"?: A Comparative Analysis of Pearl Harbor and 9/11 in History Textbooks. Issue 2 (1st September 2022) - Berman, Daniel; Stoddard, Jeremy
Abstract: In the aftermath of the 11 September 2001 attacks against the United States, people immediately compared the attack with the Japanese assault on Pearl Harbor sixty years prior. In this article, we explore how US and world history textbooks published shortly after Pearl Harbor and 9/11 depicted and contextualized both events. The textbooks demonstrate that the depictions of Pearl Harbor neatly fit within a chapter about the origins, battles and home fronts of the Second World War. However, textbooks struggled to situate 9/11, placing it within histories of terrorism, histories of the modern Middle East, or twenty-first century problems. Moreover, the textbook authors likely relied on the powerful collective memories that each event triggered because the textbook descriptions of both attacks are exceedingly brief.